South Africa’s Institutions of Higher Learning: Their “Study of Islam” Programs (American Journal of Islam and Society, 2014)
As a discipline, “Islamic studies” has attracted serious attention by a number of institutions of higher learning in predominantly nonMuslim societies. While southern Africa’s communities witnessed the inclusion of “Islam” as a subject in the faculties of theology at various regional universities as well as Christian seminaries, Muslim communities have clamored for the appointment of Muslim staff at universities to teach courses on Islam. On the whole, these educational developments bode well for the teaching and studying of Islam regionally, even though the purpose and objectives for doing so differ radically from one institution to the other. This essay first seeks to offer a brief insight into the teaching of “Islam” as a subject in theological/oriental/religious studies programs; it thereafter reflects upon “Islamic studies” as a social science discipline that has been included in the social science and humanities syllabus. It focuses on the BA Honors program to show the themes chosen for these programs and how scholars redesigned and changed these programs to meet modern needs. Apart from using “social change” as its theoretical framework, it also brings en passantinto view the insider/outsider binary that further frames the debates regarding the teaching and studying of Islam at these institutions in southern Africa generally and South Africa in particular.